If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + -1bx = 15 Solving ax + -1bx = 15 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'bx' to each side of the equation. ax + -1bx + bx = 15 + bx Combine like terms: -1bx + bx = 0 ax + 0 = 15 + bx ax = 15 + bx Divide each side by 'x'. a = 15x-1 + b Simplifying a = 15x-1 + b Reorder the terms: a = b + 15x-1
| 7-2x=6x-30 | | 11x-21=5+7x | | -21+-15=x | | -9(8x)= | | 5x/8=6 | | (-5r^4s^2)(9s^3-7r+4)= | | 5(7x-6)-4=35x-34 | | (-5r^4)(s^2)(9s^3-7r+4)= | | 2x^-2/3x | | -31=x-19 | | -7x+11=116 | | (1+100/100*(100/100-0.14)/3.4)=5 | | x-0.2=5 | | 1/2x-2/3x=4x | | 36x+6=27-3x | | (1+100/100*(100/100-0.14)/3.4) | | x-0.2x=5 | | 41x+599x-87=41(40x+61) | | -7x+11=16 | | 3x+x+7=8x-4x+7 | | 36*4/9 | | -4=k-7+1 | | -4a-27=3(7a+1)-5 | | 3(6x+9)+4x=82 | | 3x+19=13x-21 | | (1/x)+(6/(x-4))=0 | | -6(8+3x)=-102 | | 8a*4-2a*3-6a*2=0 | | 4(3x+2)+100=14x+5-2x+103 | | -14+8x=2x-6+4 | | 3n+2=(-2n)-8 | | 5(3x+4)+4x=24 |